The Exploration of Inter-Professional Relationships from the Perspective of Operating Room Students: A Qualitative Study - Pourghane, Parand; Ahmadi, Fazlollah; Abedin zadeh, Mahmood (International Journal of Engineering and Technology, 2018)
Introduction: Appropriate communication between healthcare team members and patient influences health outcomes and improves job satisfaction. There is a higher need to effective communication in the operating room due to the heavy workload. Understanding the factors affecting the relationship between healthcare professionals from the perspective of students can help design appropriate strategies for improving professional practice and the quality of care in clinical settings. The aim of this study was to explore inter-professional communication from the perspectives of operating room students using a qualitative design.Methods: A qualitative study using a conventional content analysis method was performed. Participants were consisted of bachelor degree students of operating room in university in Guilan university of Medical Sciences of Iran. They were chosen using a purposive sampling method. Semi-structured interviews were conducted for data collection until data saturation was achieved. The data was analyzed using the content analysis method suggested by Graneheim and Lundman. The criteria described by Guba and Lincoln were used for ensuring the rigor.Results: The data analysis led to the development of three themes and twelve subthemes: â€œThe effective Inter-professional communicationâ€ with the sub-themes of â€˜continuous scientific communicationâ€™, â€˜interaction managementâ€™, â€˜empathy/emotional supportâ€™ and â€˜participatory decision makingâ€™; â€œdysfunctional professional communicationâ€ with the sub-themes of â€˜limited valuesâ€™, â€˜marginalized communicationâ€™, â€˜confusion in the work loadâ€™ and â€˜destroyed preconceptionsâ€™; â€œthe clear vision of the link between professionsâ€ with the sub-themes ofÂ  â€˜the enhanced perception of selfâ€™, â€˜independence and competencyâ€™, â€˜participatory learningâ€™ and â€˜holistic care of the patientâ€™.Conclusion: According to the experiences of operating room students, providing optimal clinical conditions, enhancing cooperation and effective Inter-professional are required for improving the quality of care and protecting public health.Â Â